Analysis of Challenges of Implementation of the Strategic Management Plan in Nairobi City Water and Sewerage Company - Mogaka, Florence Kwamboka (My University, 2008)
Challenges of implementation of strategic management plan The purpose of the proposed study was to analyze the challenges of implementing the strategic management plan in Nairobi City Water and Sewerage Company Ltd. The study sought to examine the challenges of strategic plan implementation aimed at improving service delivery on timely basis, and if possible find ways of implementing the plans successfully. The focus of the study was on variables such as employee training, availability of resources, political influence, organization change among others. The researcher adopted descriptive research design. The study target was Nairobi City Water and Sewerage Company Ltd, with a target population of 928 consisting of Functional Directors, Managers and Co-ordinators, Supervisors and Officers, and Rank and File, with a sample size of 100. Questionnaires were used to collect data. The data collected was analyzed both qualitatively and quantitatively. Data were analyzed according to the objectives of the study. The overall objective of this study was to analyse challenges of implementation of the strategic management plan in NCWSC. A profile of data from each of the respondents was compiled and subjected to Statistical Package for Social Sciences (SPSS) for processing. The results are represented in tables of frequency distribution and percentages. The findings of the study showed that implementation is hampered by: political influence, inadequate employee training, inadequate provision of resources, and organisation change. In view of the above findings, the researcher made the the following four recommendations: The organization (NCWSC) would provide adequate resources to help in successful implementation of the SMP and at the same time intensify the existing training programme for the understanding of the strategy implementation process. The management should also check and control political influence by putting in place policies on recruitment and succession process.